Laminarin crude extract characterization of Sargassum sp. originated from Jepara-Indonesia with Laminarin Acid Extraction method using acetic acid solvent - Sari, Ratna Indria; Suryati, Suryati; Amalia, Indrian Rizka; Taslihan, Arief (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
Laminarin is a bioactive compound found in Sargassum sp. whose existence is widespread in Indonesia, including in Jepara, Central Java, Indonesia. Laminarin can be used in food, pharmaceutical, cosmetic, and feed industries as it is beneficial as an anti-inflammatory, antioxidant and regulates gut microbiota. This study aimed to extract laminarin from Sargassum sp. that originated from Jepara-Indonesia by laminarin acid extraction procedure with an acetic acid solvent (CH3COOH) which was safer, cheaper and easy to obtain. Characterization of laminarin crude extract use Fourier Transform Infrared (FT-IR); meanwhile, nutrition tested are moisture, ash, crude protein and crude fiber content. The results showed that laminarin extraction of Sargassum sp. from Jepara using acetic acid solvent (L-ACT) obtained the highest yield of 15.5% with a solvent ratio of 1:5 (w/v) but still lower than the yield extraction using hydrochloric acid (L-HCl) with a solvent ratio of 1:10 (w/v) that was 24.17%. FT-IR absorption band at 2359.96 cm-1 (-OH bending; transmission angle peak), 1538.54 cm-1 (C-C aromatic; carboxyl groups), 1409.35 cm-1 (C-H bending; carboxyl groups), 1230.89 cm-1 (C-O-C stretching; sugar region), 1022.58 cm-1 (R-O-R (acetal)), and at 944.94 cm-1 (O-R cyclic) of the L-ACT samples were similar to those of the L-HCl and standard laminarin references in other studies that used as a positive control, confirming the presence of laminarin. The L-ACT extract had lower ash, crude protein content and higher water content compared to L-HCl crude extract. Meanwhile, the crude fiber content in both L-ACT and L-HCL was not identified. The results showed that Sargassum sp. from Jepara was the potential source of laminarin for many industries (pharmacy, cosmetic, food), and acetic acid could be used as a suitable solvent to extract laminarin in the LAE method.